Expression of Human Endogenous Retroviruses in the Human Thymus Along T Cell Development - Passos, Vânia; Pires, Ana R.; Foxall, Russell B.; Nunes-Cabaço, Helena; Sousa, Ana E. (Frontiers in Virology, 2022)
Human Endogenous Retroviruses (HERVs) constitute up to 8% of the human genome and have been emerging as important modulators of the immune system, being associated with cancer, autoimmunity and infectious diseases. Here, we investigated the expression of three HERV families in the human thymus. HERV-K, -W, and -R envelope (env) and HERV-K gag transcriptional levels were quantified in the main thymocyte subsets, thymic epithelial cells (TECs), B cells and myeloid populations, and Env protein expression was studied in thymic tissue. We found that HERV mRNA decreased with T cell development, which was in agreement with the identification of HERV-K Env protein in CD3 negative cortical cells. These results suggest a distinct regulation of HERV expression along T cell development, prompting us to evaluate the interplay with host restriction factors and potential underlying pathways. The transcriptional levels of some HERVs were found to positively correlate with the expression of the host restriction factors APOBEC3G and SLFN11, and, conversely, a negative correlation was found with SAMHD1. Moreover, IFN-α and IFN-γ induced the upregulation of HERV-K env and gag in purified CD4 single-positive thymocytes. Additionally, we found high levels of HERV mRNAs in TECs. Overall, our data support a tight regulation of HERV expression during human T cell development, with possible implications for the process of T cell selection.